Rapid control of thyrotoxicosis for urgent thyroidectomy - Kreze, Alexander; Podlesak, Tomas; Roulova, Jana; Koskuba, Jiri (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Surgery for Grave’s disease is one possible option for definitive treatment. Thyroidectomy is performed after achieving a euthyroid state. Pre-operative preparation of the hyperthyroid patient is essential to avoid peri- and post-operative serious complications due to thyrotoxicosis mainly thyrotoxic crisis and death. The mainstay of preparation is the administration of anti-thyroid drugs. Occasionally rapid pre-operative optimization is required for special reasons (intolerance or side effects to anti-thyroid drugs or an aggravated serious disease with thyrotoxicosis). Various regimens for this aim were suggested with protocols composing various combination iodine (as a Lugol’s solution, or iopanoic acid, or ipodat sodium), steroids, usually dexamethasone and beta blockers, alternatively other options are plasmapheresis, lithium and exchange ionic resin. The restoration of hyperthyroid Grave’s disease to euthyroidism in our patient was rapidly accomplished with iodine, dexamethasone and beta blockers (at seventh day without complications). We propose a possible treatment protocol for these cases.